2019
DOI: 10.3390/bs9050052
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Metabolites Support Evidence of Autism as a Spectrum

Abstract: Objectives: It is common nowadays to refer to autism as a spectrum. Increased evidence of the involvement of steroid metabolites has been shown by the presence of stronger alterations in Kanner’s syndrome compared with Asperger syndrome. Methods: 24 h urine samples were collected from 20 boys with Asperger syndrome, 21 boys with Kanner’s syndrome, and identically sized control groups, each matched for age, weight, and height for comprehensive steroid hormone metabolite analysis via gas chromatography–mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 49 publications
3
36
1
Order By: Relevance
“…To our knowledge, this is the first study describing the markers of steroidogenesis across the whole pathway in plasma of boys diagnosed with ASD and neurotypical CTRL children. Only few studies dealing with the whole cascade of steroidogenesis have been published to this date, as majority of reports focus mostly on the narrow selection of the hormones and the bigger picture might be missing 12,22 . The human steroidogenesis is strongly age-dependent, particularly in children and pubescents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, this is the first study describing the markers of steroidogenesis across the whole pathway in plasma of boys diagnosed with ASD and neurotypical CTRL children. Only few studies dealing with the whole cascade of steroidogenesis have been published to this date, as majority of reports focus mostly on the narrow selection of the hormones and the bigger picture might be missing 12,22 . The human steroidogenesis is strongly age-dependent, particularly in children and pubescents.…”
Section: Discussionmentioning
confidence: 99%
“…This fact might be explained by precocious adrenarche leading to premature puberty described even in individuals having ASD 13,25 . Gasser et al analyzed steroid pathway in pubertal individuals, thus, sexual maturity have to be critically taken into account 12 . On the other hand, our results showed that sulfated androstanes like androsterone, epiandrosterone, etiocholanolone were lower in ASD group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations